(untitled) (International Journal of Engineering and Computer Science, 2014)
Multihop wireless relays can extend the area of network connectivity instantly and efficiently. However, due to the spatialdependence of wireless link-quality, the deployment of relay nodes requires extensive, expensive measurement, and managementefforts. This paper presents a mobile autonomous router system, (MARS) through which a relay router autonomously seeks andadjusts the best “reception” position for itself and cooperatively forms a string-type relay network with other neighboring routers.Specifically, MARS 1) accurately characterizes spatial link-quality through a new measurement technique, 2) effectively probes/optimizes node positioning via a spatial probing algorithm, and 3) maintains error-tolerant position information via an inexpensivepositioning algorithm. MARS has been prototyped with both a commodity mobile robot and a wireless router with IEEE 802.11cards. Our experimental evaluation of both the MARS prototype and ns-2-based simulation show that MARS achieves an average of 95 percent accuracy in link-quality measurements, and reduces the measurement effort necessary for the optimization of a node’slocation by two-thirds, compared to exhaustive spatial probing